From Ionogels to Biredox Ionic Liquids: Some Emerging Opportunities for Electrochemical Energy Storage and Conversion Devices. Issue 22 (4th September 2017) - Vioux, André; Coasne, Benoit
Abstract: Ionic liquids (ILs) continue to receive attention for applications in electrochemistry because of their unique properties as charge carriers (electrolytes) and redox shuttles (solar cells) and their ability to promote energy storage either electrostatically (supercapacitors) or chemically (secondary batteries). More specifically, the confinement of ILs in nanopores or the adsorption at surfaces, are considered a promising strategy for all solid‐state energy storage and conversion devices. Upon such immobilization, one benefits from the specific properties of ILs (large electrochemical window, relatively high ionic conductivity, task‐specific functionalities, etc.) combined with surface and confinement effects that can be tuned by playing with the porosity and chemical nature of the host. Here, some emerging applications of ILs in electrochemistry are first discussed: silica‐based ionogels as solid electrolytes and systems that involve carbon host substrates, as typical electrode materials in electrical double layer capacitors and lithium secondary batteries. Also, a non‐exhaustive, yet a comprehensive picture of the confinement and surface effects at play in such applications is presented. Then, the confinement of task‐specific ILs such as protonic ILs, IL lithium salts, and biredox ILs, is discussed, which paves the way for promising perspectives. Finally, some concluding remarks are reported and directions for future work are suggested. Abstract : Confinement of ionic liquids in inorganic porous hosts opens the door to modular materials that can be tuned as electrochemical devices . Some emerging applications are presented, including ionogels as solid electrolytes and carbon‐based materials for electrical double layer capacitors and lithium secondary batteries. The use of task‐specific ionic liquids such as protonic and biredox ionic liquids is also discussed.